Prevalence of Tuberculosis in District Haveli, Azad Jammu And Kashmir - Abu ul Hassan Faiz (Journal of Bioresource Management, 2020)
Tuberculosis is an infectious disease with a common occurrence in population of Azad Jammu and Kashmir. The current study was designed to find out the prevalence of TB among the general population of a less developed District Haveli. Samples were collected from different hospitals and TB centers located in district Haveli and tested through sputum smear microscopy for conformation of positive for TB. The three-year (2015 to 2018) study was conducted to record prevalence of tuberculosis in selected area of Azad Jammu and Kashmir. The trend line of prevalence was made by using (SPSS software). Results produced linear trends yearly which indicate the need for serious steps for management of this disease.